The influence of calcination temperature on structural and optical properties of ZnO-SiO2 nanocomposite by simple thermal treatment route - Alibe, Ibrahim Mustapha; Matori, Khamirul Amin; Sidek, Haj Abdul Aziz; Yazid, Yakoob; Saion, Elias; Alibe, Ali Mustapha; Zaid, Mohd Hafiz Mohd; Engku, Ali Engku Abd Ghapur; Zangina, Tasiu (Institute of Metallurgy and Materials Science of Polish Academy of Sciences, Committee of Materials Engineering and Metallurgy of Polish Academy of Sciences, 2018)
This study offers a new method to synthesize facilely willemite (Zn2SiO4) based phosphor at the temperature of 800 °C. The ZnO-SiO2 nanocomposite was calcined at different temperatures between 500 and 1000 °C. The structural, morphological and optical properties of the nanocomposite obtained at various calcination temperatures were studied using different techniques. The FT-IR, XRD and the UV-vis result confirmed the formation of willemite phase. The precursor was confirmed to be amorphous by XRD at room temperature, but upon calcination temperature at 500 °C, it was transformed into a crystalline structure. The crystallinity and the particle size of the nanocomposite increase as the calcination temperature were increased as revealed by XRD and TEM measurement. The sample exhibits a spherical morphology from 500 to 800 °C and dumbbell-like morphology above 800 °C as shown by the FESEM images. The absorption spectrum suffers intense in lower temperature and tends to shift to lower wavelength in the UV region as the calcination temperature increases. The band gap values were found to be increasing from 3.228-5.550 eV obtained between 500 to 1000 °C, and all the results confirm the formation of willemite phase at 800 °C.